2016
DOI: 10.1177/1474704916657833
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Gay Men as Defectors and Commitment to Group Defense Predict Aggressive Homophobia

Abstract: Homophobia encompasses a variety of attitudes and behaviors with distinct causal paths. We focus on aggressive homophobia, a propensity to feel anger and express aggression toward gay men. We investigated the conjecture that homosexual males might be seen, in recent Western cultures, as defectors from collective group defense. We predicted that consistent with a functional motive to punish and deter free riding, the perception of gay men as defectors would motivate aggression toward gay men. We also predicted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The survey did not include items measuring sexual or moral disgust sensitivity and was not able to control for these variables. To address this issue, we performed a reanalysis of data of an unpublished study by van Leeuwen et al (2016) with participants from the USA ( n = 462), Brazil ( n = 485), South Africa ( n = 481), and China ( n = 450). These data included items for pathogen, sexual, and moral disgust sensitivity, and items for antigay attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…The survey did not include items measuring sexual or moral disgust sensitivity and was not able to control for these variables. To address this issue, we performed a reanalysis of data of an unpublished study by van Leeuwen et al (2016) with participants from the USA ( n = 462), Brazil ( n = 485), South Africa ( n = 481), and China ( n = 450). These data included items for pathogen, sexual, and moral disgust sensitivity, and items for antigay attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…The idea that antigay bias is solely driven by the threat of unwanted sexual advances does not account for this, as perceived femininity appears to be driving homophobia more than perceived sexual orientation. Similarly, van Leeuwen et al (2016) found that participants who scored high on Anger at Gays Scale associated "gay" with terms associated with coalitional defection such as "surrender" and "flee" and "coward" more than those who scored low on the scale; they also found that other participants who scored high on a Coalitional Defense Scale wanted gay transgressors punished more harshly than heterosexual transgressors relative to those who scored low on it.…”
Section: Antigay Biasmentioning
confidence: 93%
“…), should also (or even primarily) refer to men who do not provide coalitional value (Pascoe 2005;Plummer 2001). Winegard et al (2016) and van Leeuwen et al (2016) found preliminary support for these hypotheses, suggesting that a coalitional value approach to antigay bias may prove fruitful. For example, Winegard and colleagues found that gay men were rated as less strong, less dominant, less masculine, and less good at being a soldier or a football player than were straight men.…”
Section: Antigay Biasmentioning
confidence: 98%
See 1 more Smart Citation